Among friends? On the Dynamics of Maori-Pakeha relationships in Aotearoa New Zealand - Brandt, Agnes (Vandenhoeck & Ruprecht Verlag, 2013)
Relationships are the glue that holds the world together. As the author shows, this common belief applies to ancient Greece as much as to contemporary Aotearoa New Zealand. Based on long-term ethnographic fieldwork, this anthropological study dedicates itself to the topic of friendship – this flexible type of sociality that has become increasingly significant in people’s lives throughout the world. At the core stand the friendship conceptions and life-worlds of Maori and Pakeha actors in New Zealand. By tracing out people’s "friendship worlds" in their wider societal context, the author takes up current debates surrounding issues of identity and sociality, indigeneity and diversity. By furthering our understanding of the social dynamics of friendship in New Zealand, the study not only contributes to the growing field of friendship research, it also reveals important implications for the understanding of group relations in a postcolonial, so-called "multicultural" society
V&R Unipress
Keywords: Alltag; Bikulturalismus; Freundschaft; friendship; Identitätsmuster; Maori; Multikulturalismus; Nahbeziehung; Neuseeland; New Zealand; Pakeha; Verwandtschaft